Selected Problems in Fluid Flow and Heat Transfer (2019)
Fluid flow and heat transfer processes play an important role in many areas of science and engineering, from the planetary scale (e.g., influencing weather and climate) to the microscopic scales of enhancing heat transfer by the use of nanofluids; understood in the broadest possible sense, they also underpin the performance of many energy systems. This topical Special Issue of Energies is dedicated to the recent advances in this very broad field. This book will be of interest to readers not only in the fields of mechanical, aerospace, chemical, process and petroleum, energy, earth, civil ,and flow instrumentation engineering but, equally, biological and medical sciences, as well as physics and mathematics; that is, anywhere that “fluid flow and heat transfer” phenomena may play an important role or be a subject of worthy research pursuits.